An Account of the Ruins of the Broch of Dun Telve, near Glenelg, excavated by H.M. Office of Works in 1914 - Curle, Alexander (Proceedings of the Society of Antiquaries of Scotland, 1916)
Descriptions of the broch survive from the eighteenth century when it was in a far less ruinous state. The broch survives in part to a height of 33 feet with seventeen steps leading to the upper galleries of which parts of five survive. A guard chamber and outbuildings also survive. Artefacts include three stone cups, nine pottery sherds and five whorls.